Influencia de la muestra en la relación diámetro-altura total en las plantas de Tapirira retusa Ducke en bosque natural, Puerto Almendra, Loreto, Perú – 2023 - Ramirez Gallardo, Nory Aitana (2024)
The objective of the study was to determine the influence of the sample on the diameter-total height relationship in Tapirira retusa Ducke trees in natural forest, Puerto Almendra, Loreto, Peru - 2023. The diameter and total height data of the trees were used. of Tapirira retusa Ducke with DAP ≥ 10 cm from the “El Huayo” Arboretum - UNAP; Sample 1 (M1) with 9 diameter classes were applied; sample 2 (M2) with 30 data chosen at random and Sample 3 (M3) as a representative sample with 32 data. In the result, it was observed that sample 1 had the greatest influence on the diameter - total height relationship for the Tapirira retusa Ducke trees where the allometric model with the best fit was the cubic one with a correlation coefficient П = 0,936, which indicates an excellent degree of relationship and with 88% of common variations between the diameter and total height of the species under study; The prediction equation chosen was: Y= - 29.216 + (5.632 . X) + (-0.196 . X2) + (0.002 . X3).